Cyclical elements of operators which are left-inverses to multiplication by an independent variable - Linchuk, Yu. S. (Methods of Functional Analysis and Topology, 2006)
We study properties of operators which are left-inverses to the operator of multiplication by an independent variable in the space H (G) of functions that are analytic in an arbitrary domain G. This space is endowed with topology of compact convergence. A description of cyclic elements for such operators is obtained. The obtained statements generalize known results in this direction.